2009
DOI: 10.1590/s1517-83822009000200018
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide resistance and genetic variability in plant pathogenic strains of Guignardia citricarpa

Abstract: Citrus black spot (CBS) is a plant disease of worldwide occurrence, affecting crops in Africa, Oceania, and South America. In Brazil, climate provides favorable conditions and CBS has spread to the Southeast and South regions. CBS is caused by the fungus Guignardia citricarpa (anamorph: Phyllosticta citricarpa) and its control is based on the use of fungicides, such as benzimidazoles. In South Africa, the disease was kept under control for 10 years with benomyl, until cases of resistance to high concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Strobilurin fungicides (QoI) and benzimidazoles, which are highly effective for CBS control (Goes, 2002;Goes et al, 2000;Schutte et al, 2003;Miles et al, 2004), are not currently labelled for citrus in the EU, and their future use will depend on private or public funding resources to cover the registration costs. Although the risk of resistance to QoIs is considered to be high (FRAC, 2013), molecular studies have suggested a low QoI resistance risk in P. citricarpa populations (Possiede et al, 2009;Stammler et al, 2013;Hincapie et al, 2014). Although the risk of resistance to QoIs is considered to be high (FRAC, 2013), molecular studies have suggested a low QoI resistance risk in P. citricarpa populations (Possiede et al, 2009;Stammler et al, 2013;Hincapie et al, 2014).…”
Section: Controlmentioning
confidence: 99%
“…Strobilurin fungicides (QoI) and benzimidazoles, which are highly effective for CBS control (Goes, 2002;Goes et al, 2000;Schutte et al, 2003;Miles et al, 2004), are not currently labelled for citrus in the EU, and their future use will depend on private or public funding resources to cover the registration costs. Although the risk of resistance to QoIs is considered to be high (FRAC, 2013), molecular studies have suggested a low QoI resistance risk in P. citricarpa populations (Possiede et al, 2009;Stammler et al, 2013;Hincapie et al, 2014). Although the risk of resistance to QoIs is considered to be high (FRAC, 2013), molecular studies have suggested a low QoI resistance risk in P. citricarpa populations (Possiede et al, 2009;Stammler et al, 2013;Hincapie et al, 2014).…”
Section: Controlmentioning
confidence: 99%
“…Phytopathogens do not influence only food and floricultural production but in the medicinal plant industry fungi can also affect the production and the safety of the medicinal plant after harvesting. Existing control measures are not enough to deal with emergence or outbreaks of plant fungal pathogens (Ishii, 2006;Possiede et al, 2009). Therefore, continued research, including using plant based products, is required to provide effective biological products that are cheap, less toxic and effective (Martinez, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of various synthetic chemicals in agricultural productions over the years has reduced the impact of many plant fungal diseases and increased plant crop yield and led to financial gains (Gianessi and Reigner, 2006). Since the 1970s, however farmers have been struggling with the emergence of resistance against fungicides (Ishii, 2006;Possiede et al, 2009). This leads to yield financial losses.…”
Section: Fungicidesmentioning
confidence: 99%
“…Furthermore, in vitro investigations of Possiede et al . () in G. citricarpa , the causal agent of citrus black spot, showed considerable variations in the sensitivity towards the strobilurine azoxystrobin across strains that can easily result in the selection of resistant strains.…”
Section: Disease Managementmentioning
confidence: 99%